2023
DOI: 10.1101/2023.03.14.532585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An N-acetyltransferase required for EsxA N-terminal protein acetylation and virulence in Mycobacterium marinum.

Abstract: N-terminal protein acetylation is a ubiquitous post-translational modification that broadly impacts diverse cellular processes in higher organisms. Bacterial proteins are also N-terminally acetylated, but the mechanisms and consequences of this modification in bacteria are poorly understood. We previously quantified widespread N-terminal protein acetylation in pathogenic mycobacteria (C. R. Thompson, M. M. Champion, and P.A. Champion, J Proteome Res 17(9): 3246-3258, 2018, https:// doi: 10.1021/acs.jproteome.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Previous studies have found major differences in function between recombinant ESAT-6 in general when compared with ‘native’ ESAT-6 purified from Mtb cultures, which are typically purified using much harsher techniques than recombinant protein due to the lack of affinity tags. One attractive theory for the observed difference between recombinant and native ESAT-6 which is gaining traction is N-terminal acetylation being required for ESAT-6 function, but this has not yet been proven in Mtb infection ( Aguilera et al, 2020 ; Collars et al, 2023 ; Mba Medie et al, 2014 ; Okkels et al, 2004 ). The most commonly given reason for the importance of N-acetylation is that acetylated ESAT-6 is more easily released from CFP-10 under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found major differences in function between recombinant ESAT-6 in general when compared with ‘native’ ESAT-6 purified from Mtb cultures, which are typically purified using much harsher techniques than recombinant protein due to the lack of affinity tags. One attractive theory for the observed difference between recombinant and native ESAT-6 which is gaining traction is N-terminal acetylation being required for ESAT-6 function, but this has not yet been proven in Mtb infection ( Aguilera et al, 2020 ; Collars et al, 2023 ; Mba Medie et al, 2014 ; Okkels et al, 2004 ). The most commonly given reason for the importance of N-acetylation is that acetylated ESAT-6 is more easily released from CFP-10 under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found major differences in function between recombinant ESAT-6 in general when compared with “native” ESAT-6 purified from Mtb cultures, which are typically purified using much harsher techniques than recombinant protein due to the lack of affinity tags. One attractive theory for the observed difference between recombinant and native ESAT-6 which is gaining traction is N-terminal acetylation being required for ESAT-6 function, but this has not yet been proven in Mtb infection (Aguilera et al, 2020; Collars et al, 2023; Mba Medie et al, 2014; Okkels et al, 2004). The most commonly given reason for the importance of N-acetylation is that acetylated ESAT-6 is more easily released from CFP-10 under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-associated and secreted cell lysate samples were prepared for LC-MS analysis as described (72, 73). 50 μg of each sample was prepared in 100 mM triethylammonium bicarbonate (TEAB), 5% sodium dodecyl sulfate (SDS), and 100 mM tris(2-carboxyethyl)phosphine (TCEP).…”
Section: Methodsmentioning
confidence: 99%